Development of Flipped Book Teaching Materials Based on Scientific Approach Classification of Living Things for Grade X at High School - Ayu Cantika Putri; Hartati; Faisal; Ismail (Jurnal Penelitian Pendidikan IPA, 2025)
The background of this study is based on the suboptimal biology learning process due to the limitations of teaching materials used in schools, which are generally still in the form of conventional textbooks and unguided online information searches. This study aims to develop digital teaching materials in the form of a flipped book based on a scientific approach on the subject of classification of living things for 10th grade high school students. This study employs the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model and was pilot-tested at SMA Kartika XX-1 Makassar, involving 33 students and 3 biology teachers. Data analysis included expert validation, student and teacher response questionnaires for practicality, and pretest-posttest scores to assess effectiveness. The expert validation showed a very high level of validity with a Content Validity (CV) of 1, falling into category D of relevance. The practicality test yielded an average student response of 80.9% and teacher response of 94.9%. The effectiveness test showed N-gain results with 90.91% of students in the high and moderate categories. Thus, the scientific approach-based flipped book is declared valid, practical, and effective for use as teaching material for biology in high schools.